Cost accounting : an introduction to cost management systems - Jagolinzer, Philip (Australia ; United Kingdom : South-Western College, 2000)
This book is about: Cost accounting and product manufacturing; Process costing systems; Standard costing systems; Cost allocation methods; and an Introduction to additional topics.
Keywords: Accounting; Finance; Economics; Cost accounting